Evaluation of the role of Ibadurrochman values in character building at Anwarul Huda Islamic Boarding School in Malang - Roshadah, Nur Anishatur; Fahriyan, Wahyu (Abjadia : International Journal of Education, 2025)
This study explores the implementation and evaluation of Ibadurrahman values in character education at Anwarul Huda Islamic Boarding School, Malang. Employing a qualitative descriptive method within a case study framework, data were collected through interviews, observations, and document analysis, and processed using the Miles and Huberman interactive model. The evaluation applied the discrepancy model to identify gaps between program objectives and actual outcomes, thereby informing strategic improvements. The findings indicate the use of two primary evaluation mechanisms: monthly evaluations involving both administrators and students, and periodic assessments focusing on students’ compliance with character development benchmarks. Disciplinary measures (ta’zīr) were educational in nature, emphasizing non-violent moral reinforcement through Qur’anic recitation, reflective writing, and memorization tasks. These sanctions functioned as both preventive and corrective tools, encouraging introspection and behavioral transformation. Moreover, the character education program integrated Ibadurrahman values into structured routines and daily activities, demonstrating its effectiveness in fostering a holistic moral environment. The study underscores the institution’s commitment to systematic character education rooted in Islamic ethics and offers a replicable model for similar educational settings. These findings contribute to the broader discourse on faith-based character formation and provide practical insights for Islamic educational institutions seeking sustainable and value-driven approaches.